The Diagnostic Value of Contrast‐Enhanced Vessel Wall MRI for Diagnosing Neuropsychiatric Systemic Lupus Erythematosus - Ide, Satoru; Fujita, Yuya; Murakami, Yu; Futatsuya, Koichiro; Yoshimatsu, Yuta; Tsukamoto, Jun; Oku, Haruka; Sakamoto, Toshihiro; Tanaka, Yoshiya; Aoki, Takatoshi (Journal of magnetic resonance imaging, 2025)
ABSTRACT Background Imaging biomarkers for neuropsychiatric systemic lupus erythematosus (NPSLE) are highly needed, and intracranial contrast‐enhanced vessel wall imaging (CE‐VWI) can potentially detect cerebral vessel wall abnormalities in lupus. Purpose To evaluate the diagnostic value of CE‐VWI in differentiating NPSLE from non‐NPSLE. Study Type Cross‐sectional, retrospective. Subjects Forty‐seven patients with NPSLE (mean age, 44.3 years ± 13.2 standard deviation [SD], 40 females, 85%) and 52 patients without NPSLE (mean age, 43.0 years ± 16.5 SD, 49 females, 89%). The non‐NPSLE group consisted of SLE patients who had no NP symptoms or were diagnosed with comorbidities from other diseases. Field Strength/Sequence 3‐T, three‐dimensional (3D) contrast‐enhanced vessel wall imaging (3D‐T1‐CUBE). Assessment Vessel wall lesions (VWLs) were visually assessed across 15 segments, from the internal carotid artery and basilar artery to A1–A2 for ACA, M1–M2 for MCA, and P1–P2 for PCA, for wall thickening and enhancement. Conventional MRI and MR angiography were also used to assess infarction, hemorrhage, atrophy, and arterial stenosis. Statistical Tests Paired comparisons using the chi‐square and unpaired t‐tests were followed by multivariate logistic regression analysis incorporating factors with significant group differences to identify associations with NPSLE. Receiver operating characteristic (ROC) analysis with the area under the curve (AUC) assessed the diagnostic performance of CE‐VWI. A p‐value < 0.05 was considered statistically significant. Results The NPSLE group showed a significantly higher number of contrast‐enhancing VWLs (CE‐VWLs; median [interquartile range]: 2 [0.5–4] vs. 0 [0–1]). Cerebral infarctions and arterial stenotic lesions were more common in NPSLE, occurring in 12 (26%) vs. 2 (3%) and 19 (40%) vs. 5 (9%) of patients, respectively. A multivariate logistic regression analysis identified CE‐VWLs as the sole significant factor associated with NPSLE (odds ratio, 1.97; 95% confidence interval, 1.23–3.16). The ROC analysis showed an AUC of 0.78 for CE‐VWLs, with a sensitivity of 60% and a specificity of 87%. Data Conclusion CE‐VWI may demonstrate high specificity and good diagnostic performance in differentiating NPSLE from non‐NPSLE. Evidence Level 3. Technical Efficacy Stage 2.